The Musculoskeletal Involvement After Mild to Moderate COVID-19 Infection - dos Santos, Patty K.; Sigoli, Emilly; Bragança, Lorenna J.G.; Cornachione, Anabelle S. (Frontiers in Physiology, 2022)
COVID-19, a disease caused by the novel coronavirus SARS-CoV-2, has been drastically affecting the daily lives of millions of people. COVID-19 is described as a multiorgan disease that affects not only the respiratory tract of infected individuals, but it has considerable effects on the musculoskeletal system, causing excessive fatigue, myalgia, arthralgia, muscle weakness and skeletal muscle damage. These symptoms can persist for months, decreasing the quality of life of numerous individuals. Curiously, most studies in the scientific literature focus on patients who were hospitalized due to SARS-CoV-2 infection and little is known about the mechanism of action of COVID-19 on skeletal muscles, especially of individuals who had the mild to moderate forms of the disease (non-hospitalized patients). In this review, we focus on the current knowledge about the musculoskeletal system in COVID-19, highlighting the lack of researches investigating the mild to moderate cases of infection and pointing out why it is essential to care for these patients. Also, we will comment about the need of more experimental data to assess the musculoskeletal manifestations on COVID-19-positive individuals.